Dietary index for gut microbiota, a novel protective factor for the prevalence of chronic kidney diseases in the adults: insight from NHANES 2007–2018 - Xiao, Yunfei; Yang, Yaqing; Gao, Shunyu; Zhang, Hao; Wang, Jia; Lin, Tao; Bai, Yunjin (Frontiers in Nutrition, 2025)
IntroductionThis study explore the association between the dietary index for gut microbiota (DI-GM) and the prevalence of chronic kidney disease (CKD).MethodA cross-sectional study of participants aged ≥20 years using the data drawn from NHANES (2007–2018). DI-GM is comprised 14 dietary components (10 beneficial and 4 unfavorable). CKD diagnosis based on urine albumin-to-creatinine ratio (uACR) and estimated glomerular filtration rate (eGFR). Logistic regression models were employed to evaluate the relationship between DI-GM and CKD while controlling for various covariates. Additionally, a spline smooth analysis was performed. Subgroup and interaction analyses were conducted to investigate whether any factors modified this relationship.ResultsA total of 28,843 participants were eligible for the study, of whom 5,461 were diagnosed with CKD, while 23,382 were not. Patients with CKD exhibited significantly lower DI-GM scores compared to healthy individuals. A negative association between DI-GM and the prevalence of CKD was observed across all models, with the relationship being more pronounced in individuals with DI-GM scores greater than 5 compared to those with scores ≤3. Beneficial components, such as dietary fiber, whole grains, and coffee, were identified as protective factors. Moreover, sex make an effect on this relationship, with stronger effects noted in women.ConclusionHigher DI-GM scores correlate with reduced CKD prevalence, and the effect appears to be more pronounced in women than in men. These findings suggest that enhancing gut health through diet may serve as a viable strategy for the prevention and management of CKD, with particular attention to sex-based differences in prevention.